Agent-based simulation of stock price in an artificial stock market - Toh, Daniel Cher Kiang. (2009)
The world financial markets and systems had crashed or failed several times in the previous and current century due to investors’ behaviours and attitudes as well as erratic developments on the market that arose out of such trading behaviours. The most notable examples include Wall Street crash of 1929, the dot com bubble burst and the recent US housing bubble.